Financial market in Belarus and Uzbekistan - Karachun, Irina A.; Babayeva, Nargiza M. (Journal of the Belarusian State University. Economics, 2019)
The article reveals the theoretical foundations, the essence and role of the securities market, studies its current state in the Republic of Belarus and the Republic of Uzbekistan, identifies the problems of its development and measures taken by the government to overcome them. The problems that impede the increasing role of the stock market, bringing the activities of joint stock companies to the level of international standards are analyzed. The factors that influence the expansion of the scale of investment operations of commercial banks with shares of joint-stock enterprises of Uzbekistan are studied, recommendations are given for improving the investment and financial infrastructure of Uzbekistan.